Concentration of particulate matter and its dispersion factor in surface waters of the Canary upweling region, East Atlantic - Vadim P Sivkov; Vladimir I Burenkov (PANGAEA, 1991)
Particulate matter concentration and water temperature at 5 m depth level are compared in the Canary upwelling region to the east of the Cape Blanc. It was found that accumulation of particulate matter was timed to hydrofrontal zones. Particle size distributions for particulate matter obtained using the Coulter counter agree with the hyperbolic law (of the Junge type) with double values for the size parameter, which changes for particle diameters of 5-6 microns. Average values for the size parameter in the region of the upwelling are significantly lower than in the open ocean. Specific surface of particulate matter associated with reactivity differs significantly on different sides of the upwelling front and increases beyond the upwelling.
Supplement to: Sivkov, VP; Burenkov, VI (1991): Concentration and dispersion of matter near the surface in the Canary upwelling region (based on quasi-synoptic survey materials). Oceanology, 31(6), 684-687